2023
DOI: 10.1177/0271678x231154597
|View full text |Cite
|
Sign up to set email alerts
|

A brief overview of a mouse model of cerebral hypoperfusion by bilateral carotid artery stenosis

Abstract: Vascular cognitive impairment (VCI) refers to all forms of cognitive disorder related to cerebrovascular diseases, including vascular mild cognitive impairment, post-stroke dementia, multi-infarct dementia, subcortical ischemic vascular dementia (SIVD), and mixed dementia. Among the causes of VCI, more attention has been paid to SIVD because the causative cerebral small vessel pathologies are frequently observed in elderly people and because the gradual progression of cognitive decline often mimics Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 164 publications
0
10
0
Order By: Relevance
“…Several studies with rodent models have demonstrated that ischemia associated with BCAO would result in retinal hypoxia, leading to vascular remodeling, reduced b-waves in electroretinography, photoreceptor and retinal ganglion cell degeneration, thinning of the retinal tissue, and eventually loss of pupillary reflex, impairing the visually guided behavior 60 72 On the other hand, it has been reported that BCAS model, unlike the BCAO model, did not exhibit optic nerve damage and were therefore suitable for behavioral experiments 73 , 74 . Although no data on the BCAS-induced retinal tissue oxygenation are available, several studies have reported reduced retinal vascular density in subjects with carotid stenosis 75 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies with rodent models have demonstrated that ischemia associated with BCAO would result in retinal hypoxia, leading to vascular remodeling, reduced b-waves in electroretinography, photoreceptor and retinal ganglion cell degeneration, thinning of the retinal tissue, and eventually loss of pupillary reflex, impairing the visually guided behavior 60 72 On the other hand, it has been reported that BCAS model, unlike the BCAO model, did not exhibit optic nerve damage and were therefore suitable for behavioral experiments 73 , 74 . Although no data on the BCAS-induced retinal tissue oxygenation are available, several studies have reported reduced retinal vascular density in subjects with carotid stenosis 75 …”
Section: Discussionmentioning
confidence: 99%
“… 60 72 On the other hand, it has been reported that BCAS model, unlike the BCAO model, did not exhibit optic nerve damage and were therefore suitable for behavioral experiments. 73 , 74 Although no data on the BCAS-induced retinal tissue oxygenation are available, several studies have reported reduced retinal vascular density in subjects with carotid stenosis. 75 78 Indeed, a recent study established a relationship between retinal vascular perfusion and cerebral hemodynamics in subjects with internal carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a bilateral common carotid artery stenosis (BCAS) mouse as a mouse model of CCH-induced VCI, which shows a decrease in the myelin sheath preceding neuronal dysfunction ( 9 , 10 , 27 ), similar to the human clinical picture ( 28 ). Around postoperative day 14, BCAS-operated mice do not show cognitive decline but often show a mild reduction in myelinated fiber density and a slight deficit in myelin integrity ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Around postoperative day 14, BCAS-operated mice do not show cognitive decline but often show a mild reduction in myelinated fiber density and a slight deficit in myelin integrity ( 9 ). Subsequently around postoperative day 28 after BCAS, a marked reduction in myelin sheath, “white matter damage,” and cognitive dysfunction are observed ( 9 , 27 ). To clarify the involvement of TRPA1 in CCH-induced VCI, we used genetically engineered mice: TRPA1-knockout (TRPA1-KO) and cell-specific conditional TRPA1-KO mice.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Ishikawa et al reviewed studies using the BCAS model and highlighted primary pathological mechanisms of white matter (WM) damage including chronic hypoperfusion, microvascular injury, oxidative stress, blood-brain barrier dysfunction, and neuroinflammation. 13 This may pave the way to novel treatment strategies for SIVD. In a recent BCAS study, He and colleagues showed that the antidiabetic metformin reduced WM lesions and cognitive dysfunction by ameliorating oligodendrocyte precursor cell (OPC) dysfunction.…”
mentioning
confidence: 99%